MONITORING COMPLIANCE WITH NBCAL IN PHARMACIES IN SANTA LUZIA (MG) - Cristina Gomes Nascimento, Adriana; Camargo de Sousa, Eliana; Gonçalves Teixeira, Lílian; Costa Barbosa, Cléia; Labanca, Renata Adriana (Cadernos ESP, 2024)
To monitor NBCAL in pharmacies located in Santa Luzia (MG) and evaluate the knowledge of pharmacists about this Norm. It consisted of field research carried out in 2022, in which visits were made to pharmacies observing the presence of infractions to NBCAL. Subsequently, pharmacist responsible for the establishment was advised according to the infractions found. Several infractions to NBCAL were observed in pharmacies in the municipality of Santa Luzia/MG, resulting in 75% of establishments with irregularities, as well as it was demonstrated that the knowledge about the Norm by pharmacists is superficial or in some cases non-existent. Effective monitoring is necessary to reduce irregular sales and ensure responsible consumption. Pharmacists also need more training to properly guide consumers and protect breastfeeding.
Keywords: Food Consumption; Breastfeeding; Complementary Feeding